Fatigue in Parkinson's disease: The contribution of cerebral metabolic changes. Issue 1 (29th August 2016) - Cho, Sang Soo; Aminian, Kelly; Li, Crystal; Lang, Anthony E.; Houle, Sylvain; Strafella, Antonio P.
Abstract: Fatigue is a common and disabling non‐motor symptom in Parkinson's disease associated with a feeling of overwhelming lack of energy. The aim of this study was to identify the neural substrates that may contribute to the development of fatigue in Parkinson's disease. Twenty‐three Parkinson's disease patients meeting UK Brain Bank criteria for the diagnosis of idiopathic Parkinson's disease were recruited and completed the 2‐[ 18 F]fluoro‐2‐deoxy‐D‐glucose (FDG)‐PET scan. The metabolic activities of Parkinson's disease patients with fatigue were compared to those without fatigue using statistical parametric mapping analysis. The Parkinson's disease group exhibiting higher level of fatigue showed anti‐correlated metabolic changes in cortical regions associated with the salience (i.e., right insular region) and default (i.e., bilateral posterior cingulate cortex) networks. The metabolic abnormalities detected in these brain regions displayed a significant correlation with level of fatigue and were associated with a disruption of the functional correlations with different cortical areas. These observations suggest that fatigue in Parkinson's disease may be the expression of metabolic abnormalities and impaired functional interactions between brain regions linked to the salience network and other neural networks. Hum Brain Mapp 38:283–292, 2017 . © 2016 Wiley Periodicals, Inc.